OPPORTUNITIES FOR USING ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS - Usmonxo'jayeva Sarvinoz Muxiddin qizi (PEDAGOGS, 2025)
This article explores the possibilities of using artificial intelligence (AI) in the educational process. It discusses how AI technologies can improve teaching efficiency, personalize learning, and enhance students’ creative and analytical skills. The study also highlights the importance of integrating AI tools into the education system to prepare students for the digital future.